A feminist perspective on autonomism and commoning, with reference to Zimbabwe. Issue 3 (2nd July 2016) - Alexander, Tarryn; Helliker, Kirk
ABSTRACT: This article engages with the autonomist Marxism of John Holloway from a feminist standpoint. The positions developed by this feminist critique are used to shed new light on the land occupations in contemporary Zimbabwe. Though sympathetic to his work, we argue that Holloway does not sufficiently address gender identity with specific reference to social reproduction and women. The notions of the commons and the process of commoning are consistent with Holloway's autonomist framework and its complementarities to Silvia Federici's Marxist feminist lens on the commons is highlighted. Against a tendency within autonomist and commoning theories, we argue for a pronounced identitarian politics as grounded in localised struggles undertaken by women as women. We privilege the significance of women asserting and revaluing their identities as part of a possible project of transformation. For us, struggling against and beyond what exists is invariably rooted in struggles within what exists (including identities).